The Effect of Grazing Frequency on the Performance of Some Tropical Grasses - Larbi, A. (University of Ghana, 1982)
An experiment was conducted on a grey-brown sandy-clay soil of vertical classification, at the Agricultural Research. Station, Legon, to study the effect of 3-, 4-, 5-, 6-, 8- and 10-weekly grazing on the performances of eight tropical grasses namely:- Cynodon aethiopicus, Cynodon nlemfuensis, Cynodon plectostachyus, Cenchrus ciliaris var Biloela, M git aria decumbens, Digit aria swazilandensis, Panicum. maximum and Paspalum pljcatulum. Srequent grazing reduced dry matter and green forage yields. Dry matter content, sward height, root weight and crude fiber (CP) increased with increasing grazing interval. Total ash, phosphorus, crude protein CdP) and, in vitro dry matter digestibility (IVDMD) were inversely related to increasing grazing interval Changes in calcium and calcium to phosphorus ratio wece erratic. Over a six-month period, green forage yield increased from 5.5 t/ha at 3-weekly grazing to 9 .9 t/ha, at 10-wweekly grazing. Corresponding ranges for other parameters weret dry matter yield 1 .4 to 3 .3 tAa, digestible dry matter yield 0 .8 1 to 1 .5 6 t/ha,dry matter content 24.8 to 33.5$, sward height 74 .2 to 12 4 .7cm, root weight 109.3 to 133.lg, whole-plant crude fiber, 27.2 to 31.5$, leaf CP 27.2 to 31.5$ and stem CF 32.3 to 41.5$. Crude protein decreased from 11.7$ at 3-weekly grazing to 7 .5$ at 10-weekly, in vitro dry matter digestibility, 61.4 to 47.9$, total ash 10.7 to 7.5$, calcium 0 .4 7 to 0.38$ and phosphorus 0.30 to 0.21$ for the whole-plant, leaf CP 15.0 to 11.5$, leaf IVDMD 66.3 to 56.1$; stem CP 10.4 to 4.2$, stem IVDMD 58.3 to 45.9$. P. maximum exhibited the highest dry matter yield (2.9 t/ha), digestible dry matter yield (1.72 t/ha), whole-plant CP (10.9$) and whole-plant IVDMD (62.4$). The least dry matter yield (1.8 t/ha) and digestible dry matter yield (0.90 t/ha) were recorded for C.aethiopicus. B. swazilandensis and C. nlemfuensis exhibited the least whole-plant CP (7.5$) and IVDMD (47.6) respectively. The highest whole-plant CP (37.4$) was recorded for C. ciliaris and the least (29.0$) for D. swazi1randensis. Weed infestation was low on plots of D. decumbens (1.5$) and D. swazilandensis (2.5$) and high on C. aethiopicus (9 .2$) plots. ©rasslng cycles of 5 to 6 weeks and 3 to 9 weeks are recommended for 0. aethiopicus and C. ciliaris respectively. G. nlemfuensis. C. plectostachyus, B. deocumbens, B. swazilandensis, P. maximum and P.plicatum may be graced above 10-weeks. P. maximum. B. decumbens, G. ciliaris, P. pljcatulum and C. piec to st achyus are recommended. Relative palatability decreased with increasing grazing interval. P. maximum and B. deeumbens were prefered to £. aethiopicus and B. swazilandensis. In vjvo dry matter digestibility and intake of G| nlemfuensis. 0. aethiopicus and B. swazilandensis hays harvested between 3 to 6 weeks of age ranged from 53.3 to 64.9$ and 50.4 to 69.2g/kg respectively.
Thesis(MSc)- University of Ghana